2016
DOI: 10.48550/arxiv.1609.08082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Ontology of Preference-Based Multiobjective Metaheuristics

Longmei Li,
Iryna Yevseyeva,
Vitor Basto-Fernandes
et al.

Abstract: User preference integration is of great importance in multi-objective optimization, in particular in many objective optimization. Preferences have long been considered in traditional multicriteria decision making (MCDM) which is based on mathematical programming. Recently, it is integrated in multi-objective metaheuristics (MOMH), resulting in focus on preferred parts of the Pareto front instead of the whole Pareto front. The number of publications on preference-based multiobjective metaheuristics has increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…Targeting special parts of the objective space has been largely discussed within the multi-objective optimization literature, see for example [6] or [50] for a review. The benefits of targeting a part of the Pareto front instead of trying to unveil it entirely go beyond reflecting the user's preferences: as will be shown by the experiments of Section 7, it allows an enhanced distribution of the proposed solutions within this area.…”
Section: Past Work On Targeted Multi-objective Optimizationmentioning
confidence: 99%
“…Targeting special parts of the objective space has been largely discussed within the multi-objective optimization literature, see for example [6] or [50] for a review. The benefits of targeting a part of the Pareto front instead of trying to unveil it entirely go beyond reflecting the user's preferences: as will be shown by the experiments of Section 7, it allows an enhanced distribution of the proposed solutions within this area.…”
Section: Past Work On Targeted Multi-objective Optimizationmentioning
confidence: 99%
“…Moreover, the classes and properties can also be extended and improved by means of WebProt´eg´e, which offers a shared Ontology edit platform for collaborative editing. Further use cases of the PMOEA Ontology, including visualization tool, finding appropriate method for an application, discovering opportunities for new research, can be found in [32].…”
Section: Using the Pmoea Ontologymentioning
confidence: 99%